Signatures of Selection in Composite Vrindavani Cattle of India - Singh, Akansha; Mehrotra, Arnav; Gondro, Cedric; Romero, Andrea Renata da Silva; Pandey, Ashwni Kumar; Karthikeyan, A.; Bashir, Aamir; Mishra, B. P.; Dutt, Triveni; Kumar, Amit (Frontiers in Genetics, 2020)
Vrindavani is an Indian composite cattle breed developed by crossbreeding taurine dairy breeds with native indicine cattle. The constituent breeds were selected for higher milk production and adaptation to the tropical climate. However, the selection response for production and adaptation traits in the Vrindavani genome is not explored. In this study, we provide the first overview of the selection signatures in the Vrindavani genome. A total of 96 Vrindavani cattle were genotyped using the BovineSNP50 BeadChip and the SNP genotype data of its constituent breeds were collected from a public database.  Within-breed selection signatures in Vrindavani were investigated using the integrated haplotype score (iHS). The Vrindavani breed was also compared to each of its parental breeds to discover between-population signatures of selection using two approaches, cross-population extended haplotype homozygosity (XP-EHH) and fixation index (FST). Selection of signature identifies 11 common region identified by more than one harbouring genes such as LRP1B, TNNI3K, APOB, CACNA2D1, FAM110B and SPATA17 associated with production and adaptation. Overall, our results suggested stronger selective pressure on regions responsible for adaptation compared to milk yield.